Nomen Est Omen: Heritage – Baština or Nasleđe – A (Not Merely) Terminological Dilemma - Ljiljana Gavrilović (Etnoantropološki Problemi, 2010)
This paper looks at the use of the Serbian terms "kulturna baština" and "kulturno nasleđe" (both of which are translated as "cultural heritage") to refer to elements of culture preserved from the past and considered valuable enough to be preserved as part of the musealization of reality in its various forms. It offers an analysis of how, through the (re)introduction of the old/new term baština, patriarchy and essentialism – two elements of non-material cultural heritage that are ostensibly undesirable and not to be retained since they are contrary to international law – are being reinstated in the sphere of culture by bureaucratic means.